User contribution measurement model for web-based discussion forums - Chai, Kevin; Potdar, Vidyasagar; Chang, Elizabeth (IEEE, 2009)
The success of social software depends on contributions made by two key entities; the infrastructure provider(s) and the content providers (users). Currently, social software providers do not possess a powerful and generic approach to measure the contributions of their users. The ability of measuring user contributions will allow social software providers to accurately identify, acknowledge and reward their content contributors. As a result, content providers may become motivated to contribute content more regularly. This paper proposes a user contribution measurement model which is validated against an operational web-based discussion forum.